Metal Halide Perovskite Nano/Microwires. Issue 1 (13th January 2022) - Wang, Meng; Cao, Fengren; Li, Liang
Abstract : Metal Halide Perovskite Nano/Microwires Metal halide perovskite nano/microwires (NMWs) are expected as the building blocks for nextgeneration optoelectronic devices. Their well‐defined crystal structure, fewer grain boundaries, lower defect concentration, longer photocarrier lifetime, and confined carrier transport endure them a great potential in further optoelectronic applications. More details are presented in article number 2100165 by Meng Wang, Fengren Cao, and Liang Li.